Drying kinetics of two yam (dioscorea alata) varieties (2012)
The aim of this research was the evaluation of the kinetics and the drying conditions, at laboratory scale, of two yam varieties (D. alata 9506-021 and 9506-027) from the germplasm bank of the University of Cordoba (Colombia). Two geometries (circular and square) were used for the study; the air temperature ranged from 40 to 70 °C and the air speed was 0.7 m s-1. The experimental data were fitted appropriately to Fick, Page, and Logarithmic models. Mass transfer of the yam slices was described by using Fick’s diffusion model, which was the best fitted model. Drying occurred mainly in the decline phase. Arrhenius described properly the dependency of the moisture diffusivity with temperature. Among the temperature range evaluated, moisture diffusivities varied from 1.70 x 10-9 to 6.84 x 10-10 m2/s and 1.33 x 10-9 to 6.30 x 10-10 m2/s for the D. alata 9506-21 and 9506-27, respectively. The drying activation energy for D. alata 9506-21 and 9506-27 varied from 23.19 to 25.72, and 16.03 to 17.82 kJ/mol, respectively.